THE EFFICIENCY COMPARISON BETWEEN EMERGING COMPANY MARKETS AND EXCHANGE TRADED FUNDS - Semra AYDOĞDU BAĞCI (Fırat University, 2019)
The main purpose of this study is making comparisons between the Emerging Companies Market (ECM) Company registered in Istanbul Stock Exchange and Exchange Traded Funds (ETFs) and perform effectiveness analysis over the years. In addition, the relationship between ECM and ETFs will be identified and determined whether positive or negative interaction between the two sectors is. In this context; there are 19 developing businesses registered to Istanbul Stock Exchange and 16-stock mutual fund in 2012 and 2013. In 2014 and 2015 there are 18 developing businesses registered to Istanbul Stock Exchange and 8-stock mutual fund. Ratios calculated for 2012, 2013 and 2014, 2015 years. That's because a portion of the opening of the new companies registered in the Emerging Companies Market, the lack of data and some of the investment fund and the companies went bankrupt. Therefore, 2012, 2013 and 2014, 2015 years have been determined as a common range of years. Liquid assets / total assets, total debt / total liabilities and the profitability of assets ratios are calculated with the help of 2012-2015 balance sheets and income statements of analyzed companies.